Development of Dynamic Risk-Based Inspection Using Forward Difference Approach for Pipe Failure Due to Uniform Corrosion - Fatriansyah, Jaka Fajar; Nurullia, Zahra Nadia; Federico, Andreas; Priadi, Dedi (Journal of Materials Exploration and Findings, 2023)
The oil and gas industry is one of the world's largest and most influential energy contributors. All aspects involved in the operation of this industry are fundamental to be reviewed and managed correctly, especially by preventing or minimizing the failures that could occur. Uniform corrosion is the most common component failure mechanism that can cause failure in the oil and gas industry. The company's actions in managing and preventing the risk of this type of failure have a major role in the sustainability of the company due to the possibility of more significant impacts if the risk cannot be handled well, such as high inspection and handling costs, environmental impacts, and threats to work safety. In this study, the Dynamic Risk-Based Inspection (DRBI) method, which is a development of Risk-Based Inspection (RBI), is implemented to handle and analyze risks that are managed in real-time at each inspection period. Risk level analysis was carried out through data processing related to pipe thickness from the risk profile from the inspection results in 5 months using Igor and Rstudio software and calculating corrosion rates using the forward difference approach. Based on the analysis results, five risk levels of pipeline failure at PT. X due to uniform corrosion using DRBI was obtained, consisting of two medium risks and three medium-high risks. In contrast, only one risk level was obtained from the RBI method, namely medium-high. The risk value fluctuates greatly every month, causing the DRBI method to have a higher level of accuracy and the ability to detect potential risks in more detail than the RBI method.